Azo Compounds Derived from Electrochemical Reduction of Nitro Compounds for High Performance Li‐Ion Batteries - Luo, Chao; Ji, Xiao; Hou, Singyuk; Eidson, Nico; Fan, Xiulin; Liang, Yujia; Deng, Tao; Jiang, Jianjun; Wang, Chunsheng (Advanced materials (Weinheim), 2018)
Organic compounds are desirable alternatives for sustainable lithium‐ion battery electrodes. However, the electrochemical properties of state‐of‐the‐art organic electrodes are still worse than commercial inorganic counterparts. Here, a new chemistry is reported based on the electrochemical conversion of nitro compounds to azo compounds for high performance lithium‐ion batteries. 4‐Nitrobenzoic acid lithium salt (NBALS) is selected as a model nitro compound to systemically investigate the structure, lithiation/delithiation mechanism, and electrochemical performance of nitro compounds. NBALS delivers an initial capacity of 153 mAh g−1 at 0.5 C and retains a capacity of 131 mAh g−1 after 100 cycles. Detailed characterizations demonstrate that during initial electrochemical lithiation, the nitro group in crystalline NBALS is irreversibly reduced into an amorphous azo compound. Subsequently, the azo compound is reversibly lithiated/delithiated in the following charge/discharge cycles with high electrochemical performance. The lithiation/delithiation mechanism of azo compounds is also validated by directly using azo compounds as electrode materials, which exhibit similar electrochemical performance to nitro compounds, while having a much higher initial Coulombic efficiency. Therefore, this work proves that nitro compounds can be electrochemically converted to azo compounds for high performance lithium‐ion batteries. A new chemistry is unveiled to electrochemically convert nitro compounds into azo compounds, which act as active materials to reversibly react with lithium ions. The discovery of nitro and azo compounds for organic electrodes offers new opportunities for high‐performance lithium‐ion batteries.